ANALISIS CLUSTERING UNTUK MENGETAHUI TINGKAT POTENSI TANAMAN KELAPA SAWIT BERDASARKAN LUAS TANAMAN MENGGUNAKAN ALGORITMA K-MEANS PADA BADAN PUSAT STATISTIK SUMATERA UTARA - Nuraisana Nuraisana (Jurnal Mantik Penusa, 2019)
Palm oil is an important plantation commodity plant in Indonesia, to know the number and level of potential oil palm plants need to be grouped into several groups. With the support of technological development, the ability to collect and process data is also growing. Data mining, often also called knowledge discovery in database (KDD), is an activity that involves collecting, using historical data to find regularities, patterns or relationships in large data sets. The output of data mining can be used to improve future decision making. To be able to find out the potential level of oil palm garden based on plant area from each regency in North Sumatra, a system was made to determine the level of oil palm crop production using the K-maens Clustering Algorithm Thus the results of the research are expected to help the North Sumatra Province Central Statistics Agency and in particular the North Sumatra Plantation Office to find out which areas produce the potential level of palm oil production by district.